A new genus-level and two new species-level synonyms in the extinct genus Neolitochropus Lyubarsky & Perkovsky (Coleoptera: Cyclaxyridae) - Gimme, Matthew L.; Szawaryn, Karol (Zootaxa, 2020)
Gimmel et al. (2019) recently treated the two fossil taxa of the beetle family Cyclaxyridae (Cucujoidea), a family that is today represented only by two species in New Zealand (Gimmel et al. 2009). Gimmel et al. (2019) synonymized two species from European amber described within the family Phalacridae (Cucujoidea), Stilbus bedovoyi Lyubarsky & Perkovsky, 2011 and Neolitochropus hoffeinsorum Lyubarsky & Perkovsky, 2016, with Neolitochropus bedovoyi (Lyubarsky & Perkovsky, 2011) becoming the valid combination. They treated a total of 13 specimens of this species from across Rovno, Bitterfeld, and Baltic amber deposits, implying a widespread and abundant species in Eocene Europe whose life history, like extant forms, was likely tied to sooty molds (Gimmel et al. 2019).